The development and validation of the Self-Confidence Scale (SSCS): classical test theory analysis - Suhartiwi Suhartiwi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
The cultural context of Lombok, Indonesia, presents a unique backdrop for understanding and assessing self-confidence among students. Against this backdrop, the study aims to develop a self-confidence scale specifically tailored to the cultural nuances and characteristics of the region. The research sample, comprising 244 students selected through incidental sampling techniques, reflects the diverse socio-cultural landscape of Lombok. To ensure the validity and reliability of the developed scale, the study employs rigorous validation and reliability testing methods, including the Pearson Product Moment technique for validity testing and the Alpha Chronbach technique for reliability testing. The research results show that the Suhartiwi Self-Confidence Scale (SSCS) measures student self-confidence in Lombok accurately and reliably. With correlation values from 0.313 to 0.636, all SSCS questions are legitimate. Cronbach's alpha of 0.842 indicates the SSCS's high dependability. Thus, research into culturally appropriate self-confidence scales will ensure fairness and sustainability in Lombok student self-confidence initiatives.